Ta’widh dan Ta’zir Persepektif Mufassir Klasik dan Implementasinya di Bank Syariah - Syaifullah, Hamli (MALIA: Journal of Islamic Banking and Finance, 2021)
Al-Qur'an as one of the sources of Islamic law is important to interpret. So that there is an interpretation of the al-Qur'an by an interpreter, making it able to be understood by mankind. In this regard, it becomes very relevant if the implementation of ta'widh in Islamic Banks is to be known from the perspective of the commentators. Thus, whether the application of ta'widh in Islamic banking has actually been in accordance with the maqashid of the existence of the al-Qur'an itself, which is always in accordance with the times, or is it even contradictory. Therefore, the author tries to make the views of two classical commentators, namely: Al-Baidawi in Tafsir Anwar al-Tanzil Wa Asrar al-Ta'wil and Al-Razi in Tafsir Mafatihul Ghaib relating to verses that are considered relevant to the application at a shariah bank.